2005
DOI: 10.1038/sj.onc.1208484
|View full text |Cite
|
Sign up to set email alerts
|

Arsenic trioxide (As2O3) induces apoptosis through activation of Bax in hematopoietic cells

Abstract: This study explores the roles of Bax and other Bcl-2 family members play in arsenic trioxide (As 2 O 3 )-induced apoptosis. We showed that As 2 O 3 treatment triggered Bax conformational change and subsequent translocation from cytosol to mitochondria to form various multimeric homo-oligomers in IM-9 cells. On the other hand, human leukemic Jurkat cells deficient in Bax showed dramatically reduced apoptosis in response to As 2 O 3 . Stable overexpression of Bcl-2 in IM-9 cells (IM-9/Bcl-2) inhibited As 2 O 3 -… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
59
1

Year Published

2005
2005
2012
2012

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 60 publications
(65 citation statements)
references
References 61 publications
5
59
1
Order By: Relevance
“…[2][3][4] The activity of As 2 O 3 in APL is, in part, related to the disappearance of the promyelocytic leukemia (PML)/retinoic acid receptor (RAR)a fusion protein, the gene product of the chromosomal translocation t(15,17) characteristic of APL, and the induction of differentiation. 5,6 In addition, As 2 O 3 deregulates numerous proteins through binding to sulfhydryl groups, 7 inhibits mitochondrial respiratory function 8 and induces Bax oligomerization, 9 triggering apoptosis in non-APL cell lines. Considerable evidence suggests that As 2 O 3 induces the generation of reactive oxygen species (ROS).…”
Section: Introductionmentioning
confidence: 99%
“…[2][3][4] The activity of As 2 O 3 in APL is, in part, related to the disappearance of the promyelocytic leukemia (PML)/retinoic acid receptor (RAR)a fusion protein, the gene product of the chromosomal translocation t(15,17) characteristic of APL, and the induction of differentiation. 5,6 In addition, As 2 O 3 deregulates numerous proteins through binding to sulfhydryl groups, 7 inhibits mitochondrial respiratory function 8 and induces Bax oligomerization, 9 triggering apoptosis in non-APL cell lines. Considerable evidence suggests that As 2 O 3 induces the generation of reactive oxygen species (ROS).…”
Section: Introductionmentioning
confidence: 99%
“…Multidomain pro-apoptotic members of the Bcl-2 family, Bax and Bak can facilitate mitochondrial dysfunction-mediated apoptosis, in response to various stimuli, such as cisplatin, etoposide, TRAIL (tumor necrosis factor-related apoptosis-inducing ligand), or arsenic trioxide, through homo-oligomerization dependent on their activity-related conformational changes (11,38,39). We found that ionizing radiationinduced apoptotic cell death involves induction of the apoptotic conformation and subsequent oligomerization of Bak and Bax.…”
Section: Discussionmentioning
confidence: 95%
“…This could be due to the induction of differentiation at lower dose or induction of apoptosis or autophagic cell death at higher dose [7]. Others and we have reported that arsenic at clinically achievable dosage induced apoptosis by activating mitochondrial dependent apoptosis [8,9]. It is not surprising that arsenic trioxide could disrupt multiple signaling pathways for mitogenesis, differentiation, apoptosis and cell cycle control [10,11].…”
Section: Introductionmentioning
confidence: 92%